IMF Survey, Volume 32, Issue 03. (IMF Survey; IMF Survey ;, 2003)
In preparation for the 2003 IMF-World Bank spring meetings, the IMF Executive Board will review progress on the IMF's efforts and plans to help poor countries further. The IMF Survey talked to Masood Ahmed, Deputy Director of the IMF's Policy Development and Review Department, about this effort.